The effect of meloxicam on the pharmacokinetics of beta-acetyl-digoxin. - Degner, F L (1995)
The influence of multiple-dose administration of meloxicam on the pharmacokinetics of oral beta-acetyl-digoxin was studied in 12 healthy male volunteers in a randomized double-blind two-way crossover study. The primary endpoint, Cminss, was within the accepted range for bioequivalence, as were Cmaxss and AUCss. The 90% confidence interval and the point estimator of 98.7 for Cminss were within the equivalence range of 0.8-1.25. MRT and tmax were also unchanged, while the elimination rate constant was decreased slightly by 12%, which is of no therapeutic relevance. It is concluded that co-treatment with meloxicam has no effect on the pharmacokinetics of oral digoxin.